An HPLC method for the determination of selected amino acids in human embryo culture medium - Drábková, Petra; Andrlová, Lenka; Kanďár, Roman (John Wiley & Sons Ltd., 2017)
A method for the determination of selected amino acids in culture medium using HPLC with fluorescence detection is described. Twenty hours after intra-cytoplasmic sperm injection, one randomly selected zygote was transferred to the culture medium. After incubation (72 h after fertilization), the culture medium in which the embryo was incubated and blank medium was immediately stored at -80°C. Filtered medium samples were derivatized with ortho-phthalaldehyde (naphthalene-2,3-dicarboxaldehyde), forming highly fluorescent amino acids derivatives. Reverse-phase columns (LichroCART, Purospher STAR RP-18e or Ascentis Express C18) were used for the separation. The derivatives were analyzed by gradient elution with a mobile phase containing ethanol and sodium dihydrogen phosphate. The analytical performance of this method is satisfactory for all amino acids; the intra-assay coefficients of variation were <10% and quantitative recoveries were between 95.5 and 104.4%. Changes in the levels of selected amino acids before and after human embryo cultivation were observed. After embryo incubation, the levels of all amino acids in the medium were increased, apart from aspartate and asparagine. After the cultivation of some embryos, amino acids which were not part of the medium were detected. Low amino acids turnover was observed in some embryos.
HPLC metoda pro stanovení vybraných aminokyselin v kultivačním médiu pro kultivaci lidských embryí
Keywords: amino acids; HPLC with fluorescence detection; human embryo culture medium; naphthalene-2,3-dicarboxaldehyde; ortho-phthalaldehyde; aminokyseliny; HPLC s fluorescenční detekcí; kultivační médium pro kultivaci lidských embryí; naftalen-2,3-dikarboxaldehyd, ortho-ftalaldehyd